Interfaith Marriage in Islamic Law and Positive Law in Indonesia: A Study of the Conditions and Pillars - Albab, Muhammad Ulil; Izzuddin, Ahmad (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2025)
Interfaith marriage is one of the controversial legal issues in Indonesia. Islamic Law and Indonesian Positive Law regulate the conditions and pillars of marriage differently, especially concerning the legitimacy of marriage between adherents of different religions. This research aims to compare the provisions of Islamic Law and Indonesian Positive Law regarding the conditions and pillars of interfaith marriage in Indonesia. The two main variables of the research are the valid conditions of marriage and the pillars of marriage. Through a normative juridical approach and comparative law analysis, this research examines primary legal sources such as the Qur'an, Hadith, fiqh books, and legislation, as well as secondary data from literature studies and court decisions related to the issue. The research results show convergence and divergence in these two legal systems. Islamic Law is stricter in limiting interfaith marriage, especially for Muslim women. At the same time, Indonesian Positive Law provides more flexible interpretation through administrative mechanisms such as marriage registration and temporary religious conversion. This research highlights the importance of synergy between religious law and state law in addressing interfaith marriage issues in Indonesia, as well as the social and legal impacts arising from the differences in regulations. Thus, this research contributes to developing more comprehensive marriage regulations in Indonesia. Keywords: Interfaith marriage, Islamic Law, Positive Law, marriage requirements, pillars of marriage.